2016
DOI: 10.7226/jtfm.22.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Economic Valuation As a Basis for Sustainable Mangrove Resource Management: A Case in East Sinjai, South Sulawesi

Abstract: Diversity of mangrove function generates both tangible and intangible benefits and services causing its overall value is not easily recognized hence often overlooked in coastal areas development. The study used the total economic value as a framework for estimating the values of the different uses of mangroves in East Sinjai Sub District, South Sulawesi. Survey method was carried out from September 2014 February 2015. The results showed that total value − of mangrove ecosystems in East Sinjai with total area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
0
20
0
4
Order By: Relevance
“…Mangroves covered areas were about 688 ha in 2016 (BPS Kabupaten Sinjai 2017) and distributed along the coastal and riverine zones; moreover Rhizophora sp. dominates (Suharti et al 2016). The total population of two villages was 8.370 people in 2016, and most of them were working as fishermen and shrimp farmers (BPS Kabupaten Sinjai 2017).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Mangroves covered areas were about 688 ha in 2016 (BPS Kabupaten Sinjai 2017) and distributed along the coastal and riverine zones; moreover Rhizophora sp. dominates (Suharti et al 2016). The total population of two villages was 8.370 people in 2016, and most of them were working as fishermen and shrimp farmers (BPS Kabupaten Sinjai 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Since 1980, nearly half of the total mangrove covers in the world had lost (FAO 2007). Thomas et al (2017) reported that the most significant regional mangrove loss was occurred in Southeast Asia during the period 1996-2010 (approximately 50%), corresponding to 18.4% of the global mangrove area. Also, Hamilton and Casey (2016) calculated that the deforestation of worldwide mangroves extent became lower during 2000 -2012 (from 17.3 million to 16.4 million or approximately 5%) due to increase policy intervention to rehabilitate this ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perubahan lingkungan yang muncul akibat dari degradasi mangrove menimbulkan sejumlah kerugian bagi masyarakat, seperti: peningkatan daya rusak abrasi dan pasang-surut air laut besaran nilainya. Aplikasi dari studi valuasi ekonomi sangat luas dan umumnya digunakan untuk mengestimasi nilai suatu kawasan, sebagaimana yang dilakukan oleh Lal (2003); Uddin et al (2013); Rezende et al (2015); Huxham et al (2015); dan Suharti et al (2016)…”
Section: Figure 1 Trend Of Land Cover Of Tanakeke Islandunclassified